AN INVESTIGATION OVER THE INFLUENCE OF RADIANT THERMAL MAT DIMENSIONS ON ITS RADIATIVE AND CONVECTIVE HEAT TRANSFER CHARACTERISTICS - Acikgoz, Ozgen (BEGELL HOUSE INC, 2025)
For living spaces, radiant thermal mats are seen to be a good substitute for traditional heating systems. The natural convection heat transfer properties of radiant heating and cooling systems have been well studied, while the properties of radiant mats placed on surfaces have received relatively less attention. Mats of square and rectangular shapes (a x b = 0.5 m x 0.5 m, 1 m x 1 m, 1.2 m x 1.2 m, 1.4 m x 1.4 m, 1 m x 1.2 m, 1 m x 1.4 m, and 1 m x 1.6 m) are installed on the walls of an enclosure with floor dimensions L x L = 4 m x 4 m and a height of H = 3 m in order to address this gap in the literature. Upon analyzing the complete dataset of local convective heat transfer, it is evident that there is a steady decline in the local convective heat transfer coefficients. This decline commences at the initial point of mats, which corresponds to 3 W/m2 K. This trend remains rather constant until the impact of turbulence becomes noticeably apparent, which occurs when the mat dimensions are 1 m by 1.6 m. Average convective, radiative, and overall heat transfer characteristics, which are important for building energy simulation programs, are found and correlated for different mat dimensions using the surface-to-surface (S2S) radiation model and the k-epsilon RNG turbulence model in the numerical program, with error ranges of +/- 15%, +/- 5%, and +/- 5%, respectively.
Keywords: radiant thermal mat; radiation heat transfer; average convection heat transfer coefficient; local convective heat transfer coefficient; radiant heated wall; TRANSFER COEFFICIENTS; FLOOR; Thermodynamics